Status Anak yang Dilahirkan Akibat Pembatalan Perkawinan Sedarah Menurut Hukum Islam dan Undang-Undang Perkawinan No. 1 Tahun 1974 (Studi Kasus Putusan 1160/Pdt.G/2018/PA.Bms) - Julliues Mulyadi; Hanafi Tanawijaya (Fakultas Hukum Universitas Tarumanagara, 2022)
Marriage is defined as an inner and outer relationship between a man and a woman as husband andwife with the intention of creating a joyful and eternal family or household based on the OneSupreme Godhead in Article 1 of Marriage Law No. 1 of 1974. In the context of marriage, the linkthat unites a man and a woman as husband and wife is clearly apparent. In order for each person togrow and achieve spiritual and financial well-being, husband and wife must support andcomplement one anotherLong-time residents of specific locations who are still related by blood haveengaged in incest marriages. When something is done regularly, it develops a habit, and themarriage subsequently takes on local culture. The aforementioned shows that inbreeding occurs inIslamic cultures that follow Islamic law as well as Indigenous peoples that follow customary law.Weddings with relatives or blood marriages have been restricted or even outlawed in the MarriageLaw since the passage of Marriage Law No.1 of 1974, although if this is broken and takes place, themarriage would be dissolved. Even though the prohibition of marriage has been regulated, theexistence of marriages between blood relatives, whether they happen on purpose or accidentally, isstill a phenomena in society, necessitating the annulment of marriages. Marriage annulment isdistinct from divorce. An annulment of a marriage is a ruling that declares a legally lawful marriagethat has already taken place to be null and hence to never have existed.